Efektifitas Sensor Elektrokardiograf (EKG) AD8232 Untuk Mendeteksi Kelelahan Pada Saat Penggunaan Smartphone - Teguh Wijaksana Isma; Milda Yuliza; Tuti Angraini; Roza Susanti (Teknik Elektro Politeknik Negeri Padang, 2020)
Smartphones are electronic devices that are widely used in the current modern era. Ranging from children to adults are using smartphones. Lack of knowledge from smartphone users makes the use of smartphones improperly exceeding the body's limits. This makes a variety of negative impacts of using a smartphone. One way to overcome this problem is to use an electrocardiograph (ECG) sensor. The use ECG is to determine the fatigue of smartphone users based on heart rate rhythm. The sensor used as fatigue detection is the type AD8232. The result of this process is a secure or insecure condition for using a smartphone. When BPM is worth 60 <BPM <120, the condition of smartphone users is safe, whereas when BPM <60 or BPM> 120, the condition of smartphone users is unsafe. Based on the results that have been tested, the longer the use of a smartphone, the value of the BPM will sharply be reduced.